Elimination of enzymes catalysis compartmentalization enhancing taxadiene production in Saccharomyces cerevisiae - Zhang, Chenglong; Chen, Wang; Dong, Tianyu; Wang, Ying; Yao, Mingdong; Xiao, Wenhai; Li, Bingzhi (Frontiers in Bioengineering and Biotechnology, 2023)
Taxadiene is an important precursor in taxol biosynthesis pathway, but its biosynthesis in eukaryotic cell factories is limited, which seriously hinders the biosynthesis of taxol. In this study, it is found that there was the catalysis compartmentalization between two key exogenous enzymes of geranylgeranyl pyrophosphate synthase (GGPPS) and taxadiene synthase (TS) for taxadiene synthesis progress, due to their different subcellular localization. Firstly, the enzymic-catalysis compartmentalization was overcome by means of the intracellular relocation strategies of TS, including N-terminal truncation of TS and enzymic fusion of GGPPS-TS. With the help of two strategies for enzyme relocation, the taxadiene yield was increased by 21 % and 54 % respectively, among them the GGPPS-TS fusion enzyme is more effective. Further, the expression of GGPPS-TS fusion enzyme was improved via the multi-copy plasmid, resulting that the taxadiene titer was increased by 38 % to 21.8 mg/L at shake-flask level. Finally, the maximum taxadiene titer of 184.2 mg/L was achieved by optimization of the fed-batch fermentation conditions in 3 L bioreactor, which is the highest reported titer of taxadiene biosynthesis accomplished in eukaryotic microbes. This study provides a successful example for improving biosynthesis of complex natural products by solving the critical problem of multistep enzymes catalysis compartmentalization.